Synergy of carboxymethyl cellulose stabilized nanoscale zero-valent iron and Penicillium oxalicum SL2 to remediate Cr(VI) contaminated site soil - Pan, Siyi; Tong, Jianhao; Luo, Yating; Pang, Jingli; Zhang, Haonan; Wang, Jing; Shi, Jiyan (Frontiers in Environmental Science, 2024)
Nano zero-valent iron (nZVI) acting as a high-cost disposable material in soil Cr(VI) remediation faces significant challenges due to its easily oxidizable nature and biological toxicity. In addressing this issue, the present study undertook the synthesis of a series of modified nZVI and combined the selected material with Cr(VI)-resistant filamentous fungus Penicillium oxalicum SL2 for real-site chromium pollution remediation. Adsorption experiments demonstrated that the inclusion of carboxymethyl cellulose (CMC) significantly enhanced the adsorption capacity of nZVI for Cr(VI) by 19.3% (from 73.25 to 87.4 mg/L), surpassing both biochar (37.42 mg/L) and bentonite modified nZVI (48.03 mg/L). Characterization results validated the successful synthesis of the nano composite material. Besides, oxidative stress analysis explained the unique detoxification effects of CMC on SL2, acting as a free radical scavenger and isolating layer. In real-sites soil remediation experiments, a low dosage (0.4% w/w) of nZVI/CMC@SL2 (CMC modified nZVI combined with SL2) exhibited an impressive reduction of over 99.5% in TCLP-Cr(VI) and completely transformed 18% of unstable Cr to stable forms. Notably, nZVI/CMC demonstrated its capability to facilitate SL2 colonization in highly contaminated soil and modulate the microbial community structure, enriching chromiumremoving microorganisms. In summary, the synergistic system of nZVI/CMC@SL2 merges as a costeffective and efficient approach for Cr(VI) reduction, providing meaningful insights for its application in the remediating contaminated site soils.